Young children at risk of digital disadvantage - Johnson, Genevieve (2015)
It is increasingly apparent that children who engage with digital technologies under certain conditions and in specific ways demonstrate numerous cognitive, emotional, and social advantages. Conversely, children who do not have access to emerging technologies or those who engage with technology in unhealthy ways are digitally disadvantaged. For example, children who play video games for extended periods of time and those who use the internet to isolate rather than network are at risk of social and emotional problems. The Ecological Techno-Subsystem and Techno-Microsystem provide a comprehensive conceptual framework by which to organize and interpret the large body of research on the developmental consequences of technology use during the early years of life. Such a theoretical and evidence-based foundation provides for specific interventions aimed at minimizing early childhood digital disadvantage. For example, public library internet access programs focused on promoting digital information, communication, and recreation literacy may be specifically directed toward young children residing in disadvantaged communities.